The University Belt commons a student multiplex facility which provides for the basic, educational, and recreational needs of the students in the University Belt area - Manahan, Roselle Marie S.; Ong, Simoun (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
The current situation of the University Belt is the lack of legibility and development. While the providers of needs of the students residing in the district are also not defined, the need for the general needs' providers can contribute to the redevelopment of the University Belt Area. The growing commercial industry is mainly because of the existence of the educational institutions in the area, which have helped each other, simultaneously, to grow economically. Planning the district into a "University City" while taking into account the rise in commercialization of major areas can help regulate and give more access to the students' needs and at the same time give better opportunities for the commercial/business sector of the district. The coexistence of the educational institutions and the commercial industry can create a cohesive environment wherein both industries can benefit from one another by being providers and customers at the same time. By integrating these general concepts into planning the University Town, we can create an avenue wherein students can access their needs without going outside the UBA and create a more comfortable and accessible environment for the users.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: City planning; Commercial industry; Educational institutions; University Belt